Impact of depression, anxiety, suicide on quality of life, coping and life outcome among Singapore adults - Mak, Millie Pui Yin (Nanyang Technological University, 2021)
The purpose of this study was to investigate the impact of depression, anxiety, and suicide (DAS) on the quality of life (QOL), coping and life outcome (LO) among Singapore adults, demonstrate the importance of these variables in facilitating workplace interventions, and examine the psychometric properties of the DAS measures in non-clinical settings. A sample of 327 Singapore residents, 18 to 62 years old, were recruited via convenience sampling. Participants completed a survey including a demographic form, Patient Health Questionnaire- 9 (PHQ-9), Generalized Anxiety Disorder-7 (GAD-7), Suicidal-Affective-Behavioral- Cognitive-Scale (SABCS), and a QOL, coping, and LO measure. Results showed that depression and anxiety largely predicted QOL (p = .00, f2 = 0.92) and moderately predicted maladaptive coping (p = .00, f2 = 0.23). Although depression was non-significant (p = .38) with anxiety added to the model, their combined effects moderately predicted LO (p = .00, f2 = 0.20). Suicide also had a large effect on QOL (η 2 = .25), maladaptive coping (η2 = 0.20), and LO (η2 = 0.18), p < .05. However, no significant difference (p > .05) on LO was found between moderate and high suicide risk. DAS did not predict adaptive coping or academic performance, p > .05. In conclusion, greater DAS significantly predicted a poorer QOL, more maladaptive coping and poorer LO. This paper discussed the potential value of PHQ-9, GAD-7 and SABCS, which appeared to be reliable and valid DAS measures; and the relevant factors that employers should consider when managing mental health in the Singapore workplace.